The Service of Urdu Translation and Development Committee, University of the Punjab in Promotion of Children's Literature - Dr. Ijaz Tabassum; Azhar Hussain Khan (بازیافت, 2022)
<span style="font-size: 11.0pt; line-height: 115%; font-family: "Jameel Noori Nastaleeq"; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Idara '' Taleef-o-Tarjama was established in 1962.Its aim was to convert modern knowledge into possible language.This institute translated books of different subjects.In those the books based on children psychology were also translated. Some of these are described here. In this book has been told about children's nature that how does child gets worse. On children psychology has been focused in this book. There is important information for teachers, parents and children in this book.